- - Josefina Quintero; Carmen Tulia Zuluaga; Odilia Ramírez (Universidad de Caldas, 2005)
INACMES (Action-research, Curriculum and Multimedia in Higher Education) is a group sponsored by COLCIENCIAS which has been classified under Category A. This piece of work includes the achievements of a method and a theory used to initiate the scientific formation of novice educators enrolled in the Modern Languages Program at the University of Caldas in Manizales. The project was carried out since 2004 until 2005. The extent to which novice teachers link the terms pedagogy research, curriculum and the teaching learning process is explored. The findings express concern over prescriptions from so-called beginning researchers and suggest that curriculum in higher education can contribute to the advance of pedagogical knowledge from a particular educational context which is the research work inside the formative process at the university.